Hyperadrenocorticism in dogs attended at the Animal Health Service in the City of Rio de Janeiro, Brazil - Ramos, Maria Isabel Menezes; Leal, Paulo Daniel Sant’Anna; Barbosa, Larissa Licurci de Oliveira; Lopes, Carlos Wilson Gomes (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Ramos M.I.M., Leal P.D.S., Barbosa L.L.deO. & Lopes C.W.G. Hyperadrenocorticism in dogs attended at the Animal Health Service in the City of Rio de Janeiro, Brazil. [Hiperadrenocorticismo em cães atendidos em serviço de saúde animal na cidade do Rio de Janeiro, Brasil.] Revista Brasileira de Medicina Veterinária, 38(Supl. 3):42-48, 2016. Programa de Pós-Graduação em Ciências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465 Km 7, Campus Seropédica, RJ, 23.890-000, Brasil. E-mail: mariaisabelmrm@gmail.com The hyperadrenocorticism (HAC), or Cushing’s syndrome (CS) is an endocrine disease diagnosed in dogs associated with excessive endogenous glucocorticoid by pituitary or adrenal neoplasm, by iatrogenic (IHAC) induced by excessive administration of oral glucocorticoids, parenteral or topical. These changes are identified by physical examination, no specific laboratory tests (blood counts, urinalysis, lipid profile, alkaline phosphatase dosage and liver function profiles) and confirmed by a specific test. Clinical and laboratory manifestations vary among animals due to individual differences in cortisol sensitivity, with the absence or presence of clinical and laboratory signs. Due to the importance of this disease in the dog clinic for producing systemic effects, this work had the objective of studying in 21 dogs where they were tested by stimulation of adrenocorticotropic hormone (ACTH) for HAC. Animals, which had some consistent factor for HAC as recurrent urinary tract infections, cholesterol or triglycerides and after fasting for more than 12 hours or alkaline phosphatase levels above the normal range without presenting hepatic and bone disease, they underwent adrenocorticotropic hormone stimulation test (ACTH-adrenocorticotropic hormone) synthetic dose 0.25 mL/ dog. Dogs with cortisol results after stimulation by ACTH, above 20 mcg/dL, had a confirmed diagnosis of hyperadrenocorticism. Of 21 dogs studied, 10 were diagnosed for HAC. Of these, eight dogs were positive for some species of blood parasites where six with monoinfection by Anaplasma platys and only one dog had multiple infection by A. platys and Mycoplasma canis. The hematological findings showed three dogs with anemia, four with thrombocytopenia, two with thrombocytosis, two with leukocytosis, six with eosinopenia, seven with neutrophilic, six with lymphopenia, five with monocytopenia and seven dogs with neutrophils on rods and left shunt, and six with hyperproteinaemia. Just a positive HAC dog did not have any concomitant infection. The results of biochemical evaluation showed eight animals with elevated alkaline phosphatase. Finally, when diagnosing hyperdrenocorticism in dogs, no correlation was observed with laboratory findings, other than alkaline phosphatase above 984 U/L and positive dogs for HAC.